Pengaruh Work Life Balance dan Perceived Organizational Support terhadap Kinerja Karyawan Generasi Z Kabupaten Batang - Inka Nuromavita; Luthfi Arie Widzayanto (MAMEN: Jurnal Manajemen, 2026)
This study aims to analyze the influencework life balance, And perceived organizational supporton the performance of Gen Z employees in Batang Regency. This study uses a quantitative research method. The population in this study is Generation Z who are entering the productive age of the active workforce working in companies around Batang Regency. In this study, the number of samples used is 100 respondents. Based on the results of data processing using the SPSS program, the Adjusted R Square value is 0.540. This value indicates that 54.0% of the variation in Employee Performance can be explained by the variableWork Life Balance And Perceived Organizational SupportThe remaining 46.0% is influenced by other variables outside the research model, such as work motivation, job satisfaction, work environment, leadership, compensation, organizational culture, and other factors not examined in this study. Based on the results of the hypothesis test, the variableWork life balancehas a positive and significant impact on employee performance. When work and personal life balance are balanced, it will have an impact on improving employee performance.Perceived organizational supportIt also has a positive and significant impact on employee performance. This is proven by the fact that greater organizational or company support will motivate employees to improve their performance.